RACANGAN INFORMASI PENGOLAHAN DATA OBAT PADA TOKO XYZ BERBASIS ANDROID - Darmawan, Agus; Syamsiah, Syamsiah; Setiawan, Heri Satria (Universitas Majalengka, 2023)
The ability to access and provide information very quickly and accurately is very essential for an organization, whether in the form of a commercial organization (company), university, government institution, or individual (private). The aim of this research is to create a Java-based information system and provide accurate data to shop owners with computerized transactions.The program used to support the creation of this application is a Java program, which generally consists of two basic elements, namely the Android Studio Java script and the MySQL database.After the author designed a drug data processing information system using an application. Finally, the author can draw the conclusion that with this application, it makes it easier for the performance of the xyz drug store to further improve the administration of transaction data accurately.